2011
DOI: 10.2754/avb201180040397
|View full text |Cite
|
Sign up to set email alerts
|

Chronic liver disease and subchronic nephritis in a male warty chameleon (Furcifer verrucosus) with transient hyperglycaemia – case report

Abstract: A two-year old male warty chameleon (Furcifer verrucosus) weighing 160 g was presented for veterinary examination following 4 weeks of decreased ability to catch insects with the tongue and difficulty in swallowing the prey. Non-invasive endoscopy did not reveal any macroscopic changes of the oral cavity mucosa or the cranial part of the esophagus. Dorsoventral and laterolateral plain and contrast radiographs revealed enlargement of the medial part of the liver without any visible abnormalities in the regions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…3 Several authors reported high Glu in context of diseases as suggested in a case report with a warty chameleon (Furcifer verrucosus) suffering from nephritis and in a female F. pardalis suffering from hepatic lipidosis, although the authors of the latter study do not exclude physiologic lipidosis. 10,27,29 Hyperglycemia has also been reported in reptiles with pancreatitis. 29 Because Glu was comparably high in studies with clinically healthy wild C. chamaeleon, disease as the only reason for elevated Glu appears doubtful.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…3 Several authors reported high Glu in context of diseases as suggested in a case report with a warty chameleon (Furcifer verrucosus) suffering from nephritis and in a female F. pardalis suffering from hepatic lipidosis, although the authors of the latter study do not exclude physiologic lipidosis. 10,27,29 Hyperglycemia has also been reported in reptiles with pancreatitis. 29 Because Glu was comparably high in studies with clinically healthy wild C. chamaeleon, disease as the only reason for elevated Glu appears doubtful.…”
Section: Discussionmentioning
confidence: 99%
“…10,27,29 Hyperglycemia has also been reported in reptiles with pancreatitis. 29 Because Glu was comparably high in studies with clinically healthy wild C. chamaeleon, disease as the only reason for elevated Glu appears doubtful. In the present study, chameleons showing signs of disease before, during and weeks after venipuncture were excluded from reference values.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interpretation of the disparity in uric acid and bile acids between the two turtle populations is difficult due to the uncertainty of the clinical significance of these metabolites in reptiles. Although an increase in bile acids has been demonstrated in a variety of species with chronic liver disease (Girling and Fraser 2011;Knotek et al 2011aKnotek et al , 2011b, this is not a consistent finding in all reptiles with substantial hepatic pathology (Giuseppe et al 2017). Similarly, the validity of uric acid as a method for assessing renal function in reptiles is questionable due to the fact that it is neither sensitive nor specific for renal disease and may increase in association with severe dehydration, a recent carnivorous meal or decreased temperature (Heatley and Russell 2019).…”
Section: Discussionmentioning
confidence: 99%